The remote worker's handbook : how to work effectively from anywhere - Rich, Jason (Entrepreneur Press, 2023)
"As more traditional businesses rethink the evolving workspace, adapting is imperative for the successful remote worker. Whether a seasoned professional or fresh on the scene, The Remote Worker's Handbook gives you the tools to harness an entirely new skill set for a seamless passage into the modern employment frontier"-- Provided by publisher.
Includes index.
Description based upon print version of record.
Keywords: Telecommuting.; Virtual work teams.; Équipes virtuelles.; Telecommuting; Virtual work teams